1992
DOI: 10.1002/eji.1830220735
|View full text |Cite
|
Sign up to set email alerts
|

The use of a non‐depleting anti‐CD4 monoclonal antibody to re‐establish tolerance to β cells in NOD mice

Abstract: The use of immunosuppressive drugs in the management of autoimmunity penalizes a large part of the immune system for the misdemeanors of a small minority of T cells. An ideal form of therapy would be one in which it were possible to render the immune system tolerant of the inciting antigens with minimal effects on other responses. We here show that it is possible to re-establish self tolerance in an animal model of insulin-dependent diabetes mellitus without prior deletion of CD4+ T cells using a short course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(41 citation statements)
references
References 17 publications
4
37
0
Order By: Relevance
“…These findings are consistent with several other studies in which anti-CD4 antibodies were successfully used either to retard, prevent or reverse the clinical and immunological manifestations of several murine models of autoimmune diseases such as diabetes in NOD mice [14,20,21], collagen-induced arthritis in DBA/1 mice [15], systemic lupus erythematosus (SLE) in NZB/NZW F, [11,12] and BXSB mice [13], and chronic relapsing encephalomyelitis in SJL/J [16], In these long-term experiments we have used saline rather than an irrelevant rat MoAb since the experiments of Wofsy [23] with BXSB mice showed that mice receiving rat IgG over a long period died prematurely, presumably due to T-dependent anti-rat antibodies. This cannot occur when the T cells are compromised by the anti-CD4 specificity ofthe rat antibodies [13,18], In NZB mice, the autoimmune response has previously been .shown to be T cell-dependent in vitro [10].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with several other studies in which anti-CD4 antibodies were successfully used either to retard, prevent or reverse the clinical and immunological manifestations of several murine models of autoimmune diseases such as diabetes in NOD mice [14,20,21], collagen-induced arthritis in DBA/1 mice [15], systemic lupus erythematosus (SLE) in NZB/NZW F, [11,12] and BXSB mice [13], and chronic relapsing encephalomyelitis in SJL/J [16], In these long-term experiments we have used saline rather than an irrelevant rat MoAb since the experiments of Wofsy [23] with BXSB mice showed that mice receiving rat IgG over a long period died prematurely, presumably due to T-dependent anti-rat antibodies. This cannot occur when the T cells are compromised by the anti-CD4 specificity ofthe rat antibodies [13,18], In NZB mice, the autoimmune response has previously been .shown to be T cell-dependent in vitro [10].…”
Section: Discussionsupporting
confidence: 92%
“…Administration of YTS105 blocks progression of insulitis and clinical onset in prediabetic NOD mice either in the context of spontaneous disease or in a T cell transfer model (43,44). Similarly, YTS177 is effective at preventing T1D and resolving insulitis in NOD mice after transfer of either diabetogenic splenocytes or primed BDC CD4 + T cells (35,45). The latter is associated with downregulation of IL2 and IFNG gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the striking features of such mAb-mediated tolerance is the arrest of the process whereby primed effector T cells destroy target tissues. In the NOD mouse model of IDDM, nondepleting anti-CD4 Abs have been shown to be effective in preventing IDDM even at a stage when primed T cells were already in the pancreatic islets (11). This raised the possibility that there may be a direct effect of such Ab treatment on the effector T cells and that its efficacy was not wholly attributable to inhibition of T cell priming and induction of regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that the monoclonal nondepleting rat IgG2a anti-CD4, YTS 177, can prevent spleen cells from diabetic NOD mice from transferring IDDM to irradiated NOD recipients (11). We and others have been able to demonstrate that one of the ways in which this Ab may generate and maintain peripheral tolerance is through the generation of regulatory T cells (15, 21; and reviewed in Ref.…”
Section: Yts 177 Prevents Disease Transfer By Bdc25 In Neonatal Nod mentioning
confidence: 99%
See 1 more Smart Citation